Boundaries as Spaces of Knowledge Integration: Learning from transdisciplinary collaboration on planetary health in Indonesia - Jane Wardani; Joannette J. (Annette); Diego Ramirez-Lovering; Anthony G. Capon (Elsevier, 2023)
Introduction: Deepening global inequalities in the health impacts of climate change highlight the need for transformative solutions through international and transdisciplinary collaborations. While the emerging field of planetary health provides a unique lens for recognizing interlinkages across a broader range of knowledge systems, a deeper understanding is needed about the processes through which such knowledge systems can be developed and integrated. Existing transdisciplinarity scholarship offers useful concepts of integration across boundaries; however, such understanding predominantly reflects the perspectives of Global North academic stakeholders, conceivably due to systemic power imbalance as an enduring colonial legacy. This study aims to identify opportunities for learning from the experiences of Global South stakeholders in transdisciplinary collaboration. Methods: We empirically explore the process of transdisciplinary collaboration in a case study of a large-scale planetary health research project. Through multi-method thematic analysis, this study seeks to understand Global South stakeholders' contributions, motivations, and interactions on transdisciplinary collaboration, through their experiences in the case study context. Results & Discussion: The study found that Global South stakeholders contributed a plethora of disciplinary and non-disciplinary knowledge and other resources, guided by strong cultural inclinations for collaboration. The opening up of boundary spaces was key to multi-directional knowledge integration. Analysis revealed concepts of interdependence and complementarity towards a common vision, and provides insight into stakeholders' motivations for initial and continuing engagement. Conclusion: Recognizing interdependence provides strong motivation for transdisciplinary collaboration and can help revalorize contributions from historically disadvantaged knowledge systems and stakeholders.